2‐deoxyglucose inhibits induction of chemokine expression in 3T3‐L1 adipocytes and adipose tissue explants. Issue 1 (5th October 2016) - Grant, Ryan W.; Boudreaux, Jacqueline I.; Stephens, Jacqueline M.
Abstract : Objective: To determine the influence of glycolytic inhibition on the adipocyte inflammatory response. Methods: To determine the effect of 2‐deoxyglucose (2‐DOG) on the inflammatory response, mature 3T3‐L1 adipocytes were co‐treated with 2‐DOG and LPS or TNF. To determine the effect of endoplasmic reticulum stress on TNF‐induced induction of chemokines, adipocytes were pretreated with thapsigargin or salubrinal. Chemokine mRNA levels were determined using quantitative real‐time PCR, and secretion of CCL2 was determined by Western blot. Results: 2‐DOG treatment reduced the ability of LPS and TNF to induce CCL2 mRNA levels and reduced secreted CCL2 protein levels in a dose‐dependent manner. A similar pattern of mRNA regulation was observed for other chemokines. The attenuation of TNF‐induced CCL2 mRNA levels occurred regardless of whether glucose or pyruvate was present in the media, suggesting that mechanisms other than glycolysis might mediate the observed effects. Treatment with the endoplasmic reticulum stressor thapsigargin and the endoplasmic reticulum signaling activator salubrinal reduced chemokine mRNA levels similarly to 2‐DOG. Conclusions: Collectively, our data indicate that 2‐DOG suppresses inflammatory chemokine induction in adipocytes. The effects of 2‐DOG do not seem to be linked to glycolysis but correlate with endoplasmic reticulum stress activation.